2016
DOI: 10.3892/ol.2016.4790
|View full text |Cite
|
Sign up to set email alerts
|

Association between CXCR2 and IL-22BP expression indicate a poor outcome for gastric adenocarcinoma progression

Abstract: Abstract. C-X-C motif chemokine receptor type 2 (CXCR2), a key regulatory protein, has been associated with multiple roles in the progression of numerous tumors, including gastric adenocarcinoma (GA). However, the mechanism of CXCR2 in the development of tumors remains controversial and unclear. In a previous study, the expression of CXCR2 and interleukin-22 receptor 2 (IL-22BP) was observed in GA. This promoted the present study, which aimed to explore the association between the two proteins, and to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…Moreover, the criteria to distinguish the expression level of CXCR2 were different in the enrolled studies, which might impair the veracity of the prognosis value of CXCR2. In addition, although there was unfavorable prognostic value of CXCR2 in digestive tract cancer in previous 4 studies [ 15 18 ] while the other one by Liang et al [ 15 ] reported that CXCR2 indicates a better prognosis, in this meta-analysis, it was presented that no statistical significance was detected between high and low CXCR2 expression in subgroup analysis of digestive tract cancer in this meta-analysis. Hence, it was supposed that more clinical trials focused on the prognostic value of CXCR2 in digestive tract cancer should be conducted in the future.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Moreover, the criteria to distinguish the expression level of CXCR2 were different in the enrolled studies, which might impair the veracity of the prognosis value of CXCR2. In addition, although there was unfavorable prognostic value of CXCR2 in digestive tract cancer in previous 4 studies [ 15 18 ] while the other one by Liang et al [ 15 ] reported that CXCR2 indicates a better prognosis, in this meta-analysis, it was presented that no statistical significance was detected between high and low CXCR2 expression in subgroup analysis of digestive tract cancer in this meta-analysis. Hence, it was supposed that more clinical trials focused on the prognostic value of CXCR2 in digestive tract cancer should be conducted in the future.…”
Section: Discussioncontrasting
confidence: 51%
“…The studies were conducted in 5 countries (9 Asian cohorts and 3 Caucasian cohorts), and they were published between 2012 and 2016. Studies concerning 5 digestive tract cancer (1 esophageal adenocarcinoma and squamous cell carcinoma procession cohort [ 15 ], 1 resected esophageal carcinoma cohort [ 16 ], 1 esophageal cancer cohort and 2 gastric cancer cohorts [ 17 , 18 ]) occupied the largest proportion of cancer type among all primary literatures, followed by lung cancer ( n = 2) [ 6 , 7 ], then laryngeal squamous cell carcinoma ( n = 1) [ 8 ], astrocytic tumors ( n = 1) [ 9 ], pancreatic ductal carcinoma ( n = 1) [ 10 ], clear-cell renal cell carcinoma ( n = 1) [ 11 ] and hepatocellular carcinoma ( n = 1) [ 12 ]. All studies reported the OS while only four studies reported the RFS.…”
Section: Resultsmentioning
confidence: 99%
“…IL-22RA2 is associated with antimicrobial defense, protection against injury and regeneration (Huber et al 2012). Increased expression of IL-22RA2 was reported in gastric adenocarcinoma (Yang et al 2016) and inflammatory bowel disease (Pelczar et al 2016). Up-regulated transcriptional expression of IL-22RA2 was also documented in the case of hepatitis C virus infection (Sertorio et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2 is a G protein-coupled receptor that interacts with a wide range of chemokines, especially all angiogenic glutamic acid-leucine-arginine (ELR+) CXC chemokines that mediate angiogenic activity via interacting with CXCR2 (11,12,16). Recent studies have disclosed the role of CXCR2 in tumorigenesis and progression in vivo or in vitro (13,(17)(18)(19).…”
Section: Effect Of Cxcr2 Downregulation On Chemotherapy Sensitivitymentioning
confidence: 99%